A test of the construct validity of the Triarchic Psychopathy Measure in an Italian community sample. (August 2015) - Sica, Claudio; Drislane, Laura; Caudek, Corrado; Angrilli, Alessandro; Bottesi, Gioia; Cerea, Silvia; Ghisi, Marta
Highlights: The Triarchic model tries to reconcile differing conceptions of psychopathy. This study examined reliability as well validity of the TriPM on an Italian community. Disinhibition was associated with indices of the behavioral deviance and distress. Boldness was associated with indices of adaptive function as well as maladjustment. Meanness was associated with indices of coldheartedness and antagonism. Abstract: The Triarchic Psychopathy Measure (TriPM) is a relatively new self-report measure of the basic traits thought to be associated with psychopathy: Boldness, Disinhibition and Meanness. The TRiPM was administered to 286 Italian individuals along with the Psychopathy Personality Inventory-Revised as well as measures of negative affect (anxiety, depression, stress, and hopelessness) and normal-range personality traits. The Italian TriPM showed excellent reliability and was minimally influenced by age and education. Some interesting differences emerged between males and females even though the overall pattern of correlations for TriPM scales with many criterion measures was fairly consistent across gender. TriPM Boldness was associated with indices of adaptive function as well as maladjustment. TriPM Disinhibition was most strongly associated with indices of the behavioral deviance, as well as internalizing problems. Scores on TriPM Meanness were most strongly associated with scales indexing coldheartedness, Machiavellianism, and antagonism. These findings broaden the nomological network of the Triarchic model of psychopathy.